Glycerol-induced hyperhydration does not provide cardiovascular or thermoregulatory benefit during prolonged exercise - Wendtland, C.; Nethery, V.; D'Acquisto, L.; Thomas, C. (Medicine & Science in Sports & Exercise, 1997)
The effects of glycerol-induced hyperhydration on prolonged, varied-intensity cycle ergometry were examined. Trained male cyclists (N = 8) completed two identical trials of alternating moderate and high intensity intervals for 106 min. The exercise temperature was a neutral 24 degrees Celsius. Ss were given either orange juice followed by water, or orange-juice flavored glycerol followed by water. Despite the additional fluid available, there were no differences in total sweat loss, tympanic or chest-skin temperatures, or heart rate. Implication. No cardiovascular or thermoregulatory benefits occur from glycerol and water ingestion when exercising in a thermoneutral environment despite glycerol's demonstrated capacity for fluid retention.